2002
DOI: 10.1117/12.453923
|View full text |Cite
|
Sign up to set email alerts
|

Semiconducting boron-rich neutron detectors

Abstract: Semiconducting boron-rich boron-carbon alloys have been deposited by plasma-enhanced chemical vapor deposition. Heterojunction diodes made with 276nm thick nanocrystalline layers of these alloys have been used as real-time solidstate neutron detectors. Individual neutrons were detected and signals induced by gamma rays were determined to be insignificant. Linearity of detection was demonstrated over more than two orders of magnitude in flux. The neutron detection performance was unaffected by > 1 x 10 15 neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Recent work has shown that neutron detectors and neutron voltaic devices, based on semiconducting boron carbides, may improve with some radiation exposure and are robust against radiation induced device degradation and failure. 14 The main causes for the poor neutron detection device performance are as follows: the insufficiently thick depletion region of the device, the need for a thicker device to come closer to neutron opacity, 1 and the need for better charge collection while maintaining low reverse bias leakage currents.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Recent work has shown that neutron detectors and neutron voltaic devices, based on semiconducting boron carbides, may improve with some radiation exposure and are robust against radiation induced device degradation and failure. 14 The main causes for the poor neutron detection device performance are as follows: the insufficiently thick depletion region of the device, the need for a thicker device to come closer to neutron opacity, 1 and the need for better charge collection while maintaining low reverse bias leakage currents.…”
Section: Introductionmentioning
confidence: 99%
“…Semiconducting boron car bide represents a new class of semi conducting materials with potential ap plications in neutron detection and ra dioactive decay calorimetry [1][2][3][4][5]. Neu tron detectors with boron carbide have begun to attract attention [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The small number of counts, after placing the Cd foil in position may also be the result of unsuccessfully moderated non-thermal neutrons for the PuBe source. The boron carbide heterojunctions diodes were also found to be insensitive to a 60 Co gamma source [1,2].…”
mentioning
confidence: 99%
“…Semiconducting boron carbide represents a new class of semiconducting materials with potential applications in neutron detection and radioactive decay calorimetry [1][2][3][4][5][6][7]. Boron carbide thin fi lm diodes and devices have begun to attract attention as potentially highly effi cient solid state neutron detectors [8][9][10].…”
mentioning
confidence: 99%
See 1 more Smart Citation